SAYURI’S DEFENSE MECHANISM IN ARTHUR GOLDEN’S MEMOIRS OF GEISHA - ERA KARTIKA SARI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
Abstrak Penelitian ini berfokus pada novel Athur Golden yang berjudul Memoirs of Geisha untuk menjawab : mekanisme pertahanan diri apa saja yang digunakan oleh tokoh utama? Mengapa tokoh utama menggunakan mekanisme pertahanan diri? Dengan konsep mekanisme pertahanan diri masalah akan dianalisis. Penelitian ini menggunakan mekanisme pertahanan diri untuk menghadapi kenyataan dan kecemasan tokoh utama. Kecemasan Sayuri berawal dari latar belakang keluarga dan lingkungan Sayuri. Keluarga tidak memenuhi hasratnya dan menyebabkan kekecewaann. Hasrat Sayuri untuk mendapatkan kasih sayang, rasa aman, dan kebebasan. Data ini menyajikan mekanisme pertahanan diri Sayuri untuk menghadapi kecemasannya dan dapat hidup dengan bahagia. Sayuri juga menggunakan mekanisme pertahanan diri untuk memecahkan masalahnya. Dengan mekanisme pertahanan diri Sayuri dapat beradaptasi dengan lingkungan yang baru serta menjadi seorang geisha yang terkenal. Kata kunci : Mekanisme pertahanan diri, represi, supresi, rasionalisasi, bertindak Abstract This research was conducted to explore Arthur Golden’s Memoirs of Geisha in order to answer the following research questions: what kind of defense mechanisms used by main characters? Why does Sayuri use defense mechanisms? The concept of defense mechanisms was employed as a framework for analysis. The study disclosed that Golden used repression, suppression, rationalization, and acting out because she had realistic and moral anxiety. Her anxiety was from family background and society. Her families did not fulfill her desires which brought her to have anxiety. Sayuri desired for parental love, safety and freedom. In addition, the society wanted her to follow social life which was against her desires. The society wanted Sayuri to be civilized while Sayuri herself wanted to be independent and freedom. Therefore, she repressed her anxiety in order to live peacefully. Furthermore, Sayuri used suppression because she faced unavoidably threatening situations. Sayuri had to live in the house of Okiya where she was forced to comply with social norm which was against her natural behaviors. Sayuri had conflict when she allowed the conmen to be a geisha during the journey although she did not want to. Sayuri suppressed her anxiety in order to overcome these situations. Besides, her defense mechanism also emerges as a result of her failure of her childhood when she lost her family. Importantly, defense mechanisms led the characters to experience new things and new people and helped Sayuri to reach their maturity. Keywords : Defense mechanism, repression, suppression, rationalization, and acting out INTRODUCTION Literature is one of the most creative and universal means to communicate the emotion, spiritual and intellectual concern of mankind. Sometimes most of the students feel that literature is a terrible subject and makes them nervous to study it. However, literature will be an interesting thing or not depends on their feeling of sensitivity and their imagination to enjoy the beauty of literature. In addition, literature is one way to express the creativity that reveals the interest and values of the society and frequently gives intimate and unique glimpses of how people live. (1) Statement of the problem What kind of defense mechanism is used by the main character in Arthur Golden’s Memoirs of Geisha? Why does Sayuri use defense mechanism in Arthur Golden’s Memoirs of Geisha? (2) Solving problem plan In writing the thesis, the thesis collects two types of data. They are main data and supporting data. The main data are taken from novel Memoirs of Geisha written by Arthur Golden that was published in 1999. The supporting data are taken from comments and critics about that novel which the thesis gets from internet. The thesis also taken from a lot of books as references. They are: Approach to Literature by Graham Little, Literature: Introduction to Reading and Writing by Edgar V. Robert and Henry Jacobs; A Handbook to Literature by C. Holman and William Harmon; Literature Structure, Sound, and Sense by Perrine, Peck and Cayle; An Introduction of Literature Approach by James H. Pickering, and also the psychological books that have correlation with the topic. (3) Purpose of the research To depict Sayuri’s defense mechanism in Arthur Golden’s Memoirs of Geisha, To reveal the reason why Sayuri use defense mechanism in Arthur Golden’s Memoirs of Geisha. (4) Summary about the theories This study focused on analyzing protagonists’defense mechanisms in Arthur Golden’s Memoirs of Geisha. Moreover, the results defense mechanisms the main character was included. Therefore, the theoretical framework of this study was drawn. This part consist comprises the concept of anxiety and theory of defense mechanisms. Normally when a person has some problems, she will automatically find a proper way to deal with them. However, some problems are more troublesome for some people than for other people. Those troubles lead to the anxiety state. According to James R. Gallagher and Herbert I. Harris, anxiety can occur at a deep, unconscious level and be noticed with some symptoms of physical illness. It can also happen very close to conscious level. It can be observed through body responses. For example, when an individual faces anxiety, she may have a dry mouth, rapid breathing, fast heart rate, dilate pupils or even taut muscle. This idea is similar to that of Max L. Hutt and Robert Gwyn Gibby. They state that anxiety tends to be transformed in many forms of symptomatic disturbance. It may not be able to be recognized. According to Sigmund Freud, defense mechanisms are the devices that ego defends itself against conflicts and anxieties by forcing unpleasant thoughts and impulses to the unconscious level. According to the definitions, it is obvious that defense mechanisms are psychological devices adopted by an individual to cope with frustrations, anxieties, stresses and conflicts. They can happen at the level of unconsciousness. They serve to protect the individual’s self-esteem and help extend time for direct problem solving. Appropriate use of defense mechanisms can make the individual live happily in the society. Defense mechanisms are necessary for people living in any society. They are important for personality development. To know their characteristics and functions will enable us to have a better understanding of defense mechanisms. Krench suggests the characteristics of defense mechanisms as follows. They are devices adopted to protect individual’s self-esteem and to defend against anxiety when the individual encounters continuing frustrations. They have both negative and positive aspects. For the negative aspect, they are the ways to avoid or protect the individual from anxiety. For the positive aspect, they help compensate mind and maintain self-esteem. Each device carries the same common quality which is self-deception. Then the mechanisms reveal in the form of denial of needs, feelings and situations that can cause anxiety or losing face. They can also reveal in the form of disguise of needs and motivations to substitution or reaction formation in order to be socially accepted. Normal people use defense mechanisms in some ways. An appropriate use is satisfied but an overuse is dangerous because they can cause neurotic phenomena. Each device of defense mechanism is co-related. This means the functions of each mechanism are overlapped. It is difficult to completely specify one from the others. To make it understandable, psychologists put them in categories. However, in order to cope with unpleasant feelings, the individual may have to use more than one mechanism. Naming is just to make it easy to describe. To better understand the employment of defense mechanisms, the needs of individual must be symmetrically analyzed. Defense mechanisms are not solutions for problem solving. Their function is to protect the individual from anxiety which comes from conflicts, frustrations and threatening. Apparently, it can be concluded that defense mechanisms are employed by normal people in their everyday lives. They help maintain self-esteem and protect the individual from unpleasant or undesirable feelings. They are not the solutions for a direct problem solving. The moderate use is satisfaction, but if the individual uses particular mechanism more often, it can cause mental disorder. Defense mechanisms are important for everyday life, so they have been applied to study human behaviors in research. Although many psychologists study on defense mechanisms, they give similar concepts of defense mechanisms. METHOD The thesis applies qualitative research in which the research is nor based on the statistics and mathematics, in this research, the research is focused on the depth or the quality of interaction between the concepts that is used in analyzing the topic. Since the research deals with literary work, in analyzing the topic, the thesis would like to use instric approach and extrinsic approach. According the Rene Wellek and Austen Warren in their book Theory of Literature (1756:73), intrinsic approach is an approach that emphasizes elements of literature itself. It covers plot, character, conflict, and so on. It can be concluded that instrinsic approach is the approach which is focused on the elements of the novel itself, such as plot, character, conflict. Rene Wellek and Austen Warren in their book Theory of Literature (1756:73), extrinsic approach is the approach that concerns other fields of study. It means that extrinsic approach is used to analyze the literary work by connecting the work with other fields of study, such as sociology, anthropology, psychology, religion, or other sciences. In analyzing this topic, the thesis apllies psychological approach, because in answering the statement of the problem, the thesis needs psychological knowledge since the problem concerns with human psychology. In writing the thesis, the thesis collects two types of data. They are main data and supporting data. The main data are taken from novel Memoirs of Geisha written by Arthur Golden that was published in 1999. The supporting data are taken from comments and critics about that novel which the thesis gets from internet. The thesis also taken from a lot of books as references. They are: Approach to Literature by Graham Little, Literature: Introduction to Reading and Writing by Edgar V. Robert and Henry Jacobs; A Handbook to Literature by C. Holman and William Harmon; Literature Structure, Sound, and Sense by Perrine, Peck and Cayle; An Introduction of Literature Approach by James H. Pickering, and also the psychological books that have correlation with the topic. In collecting data, the thesis condacts library research that is the research that is done in library and in the room. In this research all the main data and the supporting data are taken by close reading. When reading the books, This study make quotations and notes from the books. After the data have been collected,the study are select and classfies the data related to the topic. The data that have been selected and classified are anlyzed by interpreting them. All the data are explained and described clearly. The thesis applies the deductive and inductive method of writing. According to Graham Little (1966:201) in Approach to Literature state: “ Deducative is the process is reasoning from the general principles to particular conclussion. Inductive is the opposite process one in which many examples are considered, leading to the formation of a general principles in summary of all the evidence.” The quatation means that deductive method is done by presenting general idea which is proved by the quotations. While, inductive method is written by presenting, the quotation which is explained by statements. ANALYSIS AND RESULT Sayuri’s Defense Mechanism in Arthur Golden’s Memoirs of Geisha Psychologically, the characters in novel Memoirs of Geisha always haunted by anxiety, psychological conflict, powerless to face reality in external of her self (environment). Moreover, in data analysis, the writer focuses on certain characters who are dominating the plot of the story on novel Memoirs of Geisha. Besides that, she fulfill rules and regulations to be analyzed from Freudian psychoanalytic theory because having tragic and dramatic psychological process. In this analysis, this research is about the defense mechanism to cover someone’s feeling from tension. It is used by Sayuri who is the main character of this novel. Defense mechanism appears because of some reasons that make people feel in danger. It is a way to protect people from unpleasant emotions and keep unwanted thoughts from the unconscious mind. In this novel, the main character Sayuri uses some defense mechanisms to protect her from any kind of conflicts that occur in her life. Here, Sayuri has identified four types of defense mechanisms in this study. Sayuri’s Id In tracing Sayuri’s life, it found that she has both realistic and moral anxiety. Sayuri’s realistic anxiety comes from her family and society while her moral anxiety is from her moral awareness. In the beginning of the story, Golden describes Sayuri as a child who was sold by Mr.Tanaka. In addition, the human instinct of Sayuri comes up in the form of looking for herself, asking herself and seeking for answer how I was sold and why?